Legal Protection for Children as Criminal Offenders in the Field of Information and Communication Technology - Maghfirah, Indah; Dimara, James Aquila; Al-Mugarip, M. Haikal; Maimun, Farel Zaki; Kadir, Syukron Abdul (Formosa Journal of Social Sciences (FJSS), 2024)
Currently, information technology, apart from having an impact on progress for civilization and human welfare, is also a relevant way to carry out unlawful actions. These unlawful acts use various methods such as identity fraud, online gambling, extortion, hacking, child pornography, and intellectual property theft. With the increasing number of criminal acts involving technology and information, many minors have become perpetrators of criminal acts based on information and communication technology. However, the handling of cases where minors are the perpetrators of criminal acts is different from the handling of cases where people who are old enough (adults) are the perpetrators of criminal acts. The protection of minors is regulated in Article 34 of the 1945 Constitution which states that the State guarantees protection for the poor and neglected children. The Declaration of Children's Rights also states that children with physical and mental immaturity require special care and protection, including appropriate legal protection before or after birth. Violations of these norms do not only occur in people who are legally competent (adults), but minors are also not free from behavior that goes out of bounds or often violates the law